A Rare Case of Chronic Anogenital Ulcerations and Polymicrobial Pelvic Infections: Diagnosis and Management - Mendoua, Michèle Florence; Nkoro, Grâce Anita; Nguizaye, Lucie; Akam, Vanina Ngono; Um, Esther Ngo (New Advances in Medicine and Medical Science Vol. 9, 2023)
This chapter highlights about a case of Chronic Anogenital Ulcerations and Polymicrobial Pelvic Infections. Chronic genital ulceration is defined as a loss of superficial substance more or less deep leaving at least the dermis uncovered (erosion) and sometimes interesting the medium or deep dermis (ulceration). They will be called chronic when their evolution is greater than a month. We receive in gynaecological consultation, a 26-year-old patient G1P1001, presenting a menstrual cycle without abnormalities, with a history of unprotected vaginal sex with a 44-year-old partner of whom she was unaware of the positive character of the HIV serological status before the consultation. The physical examination reveals a hypogastric sensitivity to deep palpation, the presence of a superinfected anogenital ulceration exposing the deep dermis covered with purulent serosities, particularly involving the labia minora, the posterior vaginal fork, the anal region, the clitoris, and an extension of the lesions to the gluteal fold. The right inguinal fold exhibited a satellite lymphadenopathy, as was discovered. A protocol was put in place: the first step consisted of seat baths, antifungi and antibiotics administration: fluconazole 150 mg and tinidazole 2g in single doses, then josamycin 1 g/24h in two doses per os for two weeks. The second stage consists of the administration of doxycycline 200 mg for 21 days, Aciclovir 500 mg for 10 days, and the administration of ARV (Tenofovir + Lamivudine + Dolutegravir) or one tablet daily. The clitoris, the labia majora and labia minora, and the posterior vaginal fork gradually heal over time. In cases of chronicity, a biopsy to look for a tumour process is not necessary if the patient responds well to treatment and heals properly. A likely immune reconstitution syndrome can be used to explain why the patient passed away two weeks after starting ARV therapy. The polymicrobial character shows that there may be an interaction between the different STDs. In case of chronicity, a biopsy in search of a tumour process is not mandatory when there is a satisfactory response to treatment and good healing.